SETTING UP BLENDED LEARNING AT SCHOOL: LEADERSHIP PERSPECTIVE - Kokare, Maija; Strautins, Karlis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Effective, meaningful and balanced use of information communication technologies (ICT) for teaching and learning is essential for meeting challenges of 21st century; however, practices of blended learning (a combination of face-to-face and online instruction) in Latvia are rather developed by particular teachers than organized as evidence-based policies of ICT integration in teaching and learning at schools. The research is aimed to explore the issues related to setting up blended learning as school policy from leadership perspective, and is designed as the case study by combining: 1) piloting results of the program “Curriculum design for Blended Learning” for leadership teams (5 secondary schools in Latvia); 2) developing the self-evaluation tool for school readiness for blended learning; 3) analysis of the main leadership challenges for setting up blended learning in schools. The study results contribute ongoing processes of introducing blended learning at schools by linking both leadership, management and pedagogical perspectives.